Pengaruh Kitosan Cangkang Udang Putih (Penaeus merguiensis) terhadap Jumlah Sel Osteoblas Tulang Femur Tikus Wistar Betina Pasca Ovariektomi (The Effect of White Shrimp (Penaeus merguiensis) Shells Chitosan on the Total Osteoblast of Femoral Female Wista - Garinda Chaesaria; Muhammad Hasan (Pustaka Kesehatan, 2015)
One of imbalance disorders of bone formation is osteoporosis. This frequently occurs in postmenopause women because of estrogen deficiency that leads to an increase in osteoclast cell differentiation exceeds osteoblast cell differentiation. Shrimp shell is an export waste that can be used to produce chitosan. Chitosan can increase osteoblast cell differentiation and inhibit the differentiation of osteoclast cell in the bone formation process. The study aimed to determine the effect of chitosan white shrimp shell on the total osteoblasts of femur female wistar rats after ovariectomy. This research was the quasi experimental laboratories research by using female wistar rats that divided into three groups; a non-ovariectomy control, a negative ovariectomy, and an ovariectomy treatment group that was given chitosan 0,05 g/day. After 14 days, the experimental mice were euthanized and osteoblast was calculated. There were 43 osteoblast cells in the control group, 21 osteoblast cells in the negative control group, and 38 osteoblast cells in the treatment group. The data was analysed using one way ANOVA and showed a significant differences between all groups (0,000). It can be concluded that the chitosan of white shrimp shell can increase the osteoblasts femur female wistar rats after ovariectomy.   Keywords: osteoporosis, chitosan, osteoblast cell